AI-Enabled Piezoelectric Wearable for Joint Torque Monitoring - Jinke Chang; Jinchen Li; Jiahao Ye; Bowen Zhang; Jianan Chen; Yunjia Xia; Jingyu Lei; Tom Carlson; Rui Loureiro; Alexander M. Korsunsky; Jin-Chong Tan; Hubin Zhao (Nano-Micro Letters)
Highlights Artificial intelligence-enabled wearable device with boron nitride nanotubes (BNNTs)-based piezoelectric film for accurate joint torque sensing. Inverse-designed structure optimizes biomechanical compatibility for enhanced knee motion tracking. High-sensitivity BNNTs/polydimethylsiloxane composite enables precise and dynamic knee motion signal detection. Lightweight neural network processes complex signals for accurate torque, angle, and load estimation. Real-time monitoring system provides instant knee torque assessment for daily use.